ANALISIS PERKEMBANGAN MOTORIK KASAR PADA MATA PELAJARAN PJOK SISWA SEKOLAH DASAR - Aldi Fuaidi Hasibuan; Seifani Fadilla; Xanana Briliyan Silalahi; Nicholas Stevenly Austin Sinaga; Estomihi Hotasi Gultom; Amansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Gross motor development is an important aspect of elementary school students' growth and development, supporting their motor skills, physical fitness, and daily activities. This skill involves the use of the body's large muscles in various motor skills, such as walking, running, jumping, throwing, catching, and maintaining balance. Physical Education, Sports, and Health (PJOK) plays a crucial role in developing students' gross motor skills through various structured physical activities. This study aims to describe the gross motor development of elementary school students in PJOK learning based on published research results. This study used a literature review method with a library research approach. Data were obtained through a search of scientific articles on Google Scholar using the keywords